The Creation of Health Content on Social Media to Attract Public Interest in Health Literacy - Ali, Mohammad (BPJS Kesehatan, 2024)
This research aims to analyse health content creation on social media to attract public interest in health literacy. Because social media is considered a medium of entertainment, health education is a medical approach. The method used in this research is qualitative, and data collection is a review of journals, books, and other relevant sources for this research. The data analysis is done by reviewing each data source and analysing the correlation with the research. The results showed that creating health content on social media is an effort to attract public interest in health literacy because social media is a medium of entertainment in interacting and sharing information. People are interested in getting information from social media due to the creation of exciting content such as YouTube, x / Twitter, TikTok, Instagram, and other media. The efforts to create health content on social media are because social media has good effectiveness and can be used as a medium for promotion and health education. In addition, communication is part of the success of health policy. It is appropriate for every individual to pay attention to health factors as primary needs in their lives.